A renewable pathway towards increased utilization of hydrogen in diesel engines. (14th February 2020) - Verma, Saket; Suman, Abhishek; Das, L.M.; Kaushik, S.C.; Tyagi, S.K.
Abstract: In the present work, dual fuel operation of a diesel engine has been experimentally investigated using biodiesel and hydrogen as the test fuels. Jatropha Curcas biodiesel is used as the pilot fuel, which is directly injected in the combustion chamber using conventional diesel injector. The main fuel (hydrogen) is injected in the intake manifold using a hydrogen injector and electronic control unit. In dual fuel mode, engine operations are studied at varying engine loads at the maximum pilot fuel substitution conditions. The engine performance parameters such as maximum pilot fuel substitution, brake thermal efficiency and brake specific energy consumption are investigated. On emission side, oxides of nitrogen, hydrocarbon, carbon monoxide and smoke emissions are analysed. Based on the results, it is found that biodiesel-hydrogen dual fuel engine could utilize up to 80.7% and 24.5% hydrogen (by energy share) at low and high loads respectively along with improved brake thermal efficiency. Furthermore, hydrocarbon, carbon monoxide and smoke emissions are significantly reduced compared to single fuel diesel engine operation. Exhaust gas recirculation (EGR) has also been studied with biodiesel-hydrogen dual fuel engine operations. It is found that EGR could improve the utilization of hydrogen in dual fuel engine, especially at the high loads. The effect of EGR is also found to reduce high nitrogen oxide emissions from the dual fuel engine and brake thermal efficiency is not significantly affected. Highlights: Biodiesel-H2 dual fuel operation of the diesel engine has been experimentally studied. Performance features with maximum pilot fuel substitution and emissions are analysed. Biodiesel showed better pilot fuel substitution at low load and low emission. It was possible to significantly reduce NOx emissions at high load using EGR.